Rapid direct conversion of bovine non-adipogenic fibroblasts into adipocyte-like cells by a small-molecule cocktail - Sun, Longfei; Zhang, Dandan; Qin, Liangshan; Liu, Quanhui; Wang, Guodong; Shi, Deshun; Huang, Ben (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The molecular regulation mechanism of fat deposition in bovine and its improvement on beef quality are important research directions in the livestock industry. The research of molecular mechanisms that govern the regulation and differentiation of adipocytes may conduct to understand the mechanism of obesity, lipid disorders, and fat deposition. In the recent decade, small-molecule compounds have been widely used in reprogramming and transdifferentiation fields, which can promote the induction efficiency, replace exogenous genes, or even induce cell fate conversion alone. Furthermore, small-molecule compound induction is expected to be a novel approach to generate new cell types from somatic cells in vitro and in vivo. Methods: In this study, we established rapid chemically induced platform for transdifferentiation of bovine ear fibroblasts into adipocyte-like cells using a small-molecule cocktail (Repsox, VPA, TTNPB). The chemically induced adipocytes (CiADCs) were characterized by lipid staining, qRT-PCR and WB. Bovine natural adipocytes were used as positive control, and the expression of adipocyte-related marker genes in CiADCs were analyzed. Moreover, RNA-Seq explore the mechanism of RVB in the regulation of Bovine adipocyte transdifferentiation. Results: In this study, the chemically induced adipocytes (CiADCs) could be identified as early as day 6. The CiADCs appeared to be circular and rich of lipid droplets. The adipocyte-specific genes of LPL, PPARγ, IGF1, GPD1, C/EBPδ, ADIPOQ, PCK2, FAS, C/EBPβ, PPARGC1A, C/EBPα, and CFD were detected to be significantly upregulated in both CiADCs and natural adipocytes. Western blot analysis also confirmed the increase C/EBPα and PPARγ protein level in induced adipocytes (CiADCs-6d) treated with RVB. In addition, we also found that the signaling pathways (PPAR signaling pathway, PI3K-Akt signaling pathway, p53 signaling pathway, MAPK signaling pathway, and ECM-receptor interaction) regulated by the DEGs played a vital role in adipogenesis. Discussion: In the present study, a combination of small-molecule compounds RVB was used to transdifferentiate bovine ear fibroblasts into the chemically-induced adipocyte cells (CiADCs) that have a large number of lipid droplets. Importantly, the small-molecule cocktail significantly shortened the reprogramming turnaround time. The morphology of CiADCs is close to the “ring type” of natural differentiated adipocytes on sixth day. And, the CiADCs showed similar adipocyte-specific gene expression patterns to natural adipocytes. Furthermore, RVB increased protein expression of PPARγ and C/EBPα in the chemically-induced adipocytes (CiADCs-6d). Our findings reveal that the signaling pathways of C/EBPα and PPARγ play pivotal roles in this transdifferentiation process. In addition, we also found that the signaling pathways (PPAR signaling pathway, PI3K-Akt signaling pathway, p53 signaling pathway, MAPK signaling pathway, and ECM-receptor interaction) regulated by the DEGs played a vital role in adipogenesis. In general, this study provides valuable evidence to deepen our understanding of the molecular mechanism of small molecule cocktails in regulating adipogenesis.